‘Another brick in the wall’. On the origins of nationalism in the ‘new’ federal states of Germany - A. V. Belinskii; M. V. Khorol’skaya (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
A relatively broad support enjoyed by the populist and nationalist parties and movements (AfD, National Democratic Party of Germany, PEGIDA), as well as a higher rate of hate crimes in the eastern part of the Federal Republic of Germany raise a question on the nature of nationalism in this region. The present paper examines the causes of widespread xenophobic and nationalist sentiments in the ‘new’ federal states. To this end, the authors address a wide range of social-political and psychological factors, focusing on the historical roots and causes of the recent rise of nationalism in East Germany. Particularly, the authors show that the right-wing parties took advantage of popular frustration caused by the collapse of the East German economy after the country’s reuniﬁcation and massive unemployment by putting all the blame on migrants. Nevertheless, the causes of growing xenophobia in East Germany were far from being solely economic. For example, the authors underline the role of the politics of memory in the GDR and primarily the approaches of its leaders to the issues of the Nazi past and their attempts to draw on the country’s history to shape a new national identity. However, the failure of the state to provide an unbiased view on the national history, rigid oﬃcial ideology and its alienation from the popular demands have led to the growing nationalism in the GDR. Besides, a number of other aspects is pointed out which have also fostered xenophobic sentiments in this part of the country. Unlike West Germany which started to accept labour migrants from Italy, Turkey and Yugoslavia back in 1950s, the GDR saw few foreigners and contacts between them and local population were limited. As a result, the paper not only helps to create a more detailed image of the East German nationalism but also to identify the underlying causes of the growing popularity of right-wing populist parties and movements in the FRG, most notably, the unﬁnished process of the country’s reuniﬁcation and structural imbalances between the ‘old’ and the ‘new’ federal states.